Britain's religion and belief landscape - Rodell, Jeremy (2020)
An overview of the scale and multi-dimensional nature of the current change in British religious belief, belonging and identity with a concluding reflection from a humanist perspective.
Keywords: Christianity; Humanism; Islam; Change; no-belief; Religious Belief; Religious Identity; Secularism